CHRISTIAN RELIGION AND COUNSELLING FOR VALUE RE-ORIENTATION IN POLITICAL LEADERSHIP - ADA ANYEBE (International Studies Journal)
Christian religion by its nature inspires feelings of godliness, integrity, honesty. perseverance, goodness, rectitude, brotherly kindness, love, peace with God, and with others. This may be a powerful instrument for fostering honesty in our political leadership. Politics from every indication is the pursuit, possession, and exercise of power in a society as well as the ability to impact the society uprightly. There is always a meeting point between Christian religion and counseling for re-orientation in political leadership. Religion no doubt has been a strong determining factor when it comes to the issue of governance and policy formulation. Looking at Nigeria, for example, we have Christian religion as one of the dominant religions which affects political leadership and the effect could be positive or negative. Many studies have been undertaken on the relationship between Christian religion and counseling for value re-orientation in political leadership, however, the aspect of the direct effect of Christian religion on counseling for value re-orientation is somehow neglected. This neglect has prompted this study which is aimed at exploring the effect of Christian religion on counseling for value re-orientation in political leadership in Nigeria. The study relies mainly on data obtained from secondary sources such as publications of relevant agencies, newspapers, unpublished works, and internet materials. The data will be contextually analysed to provide insight in terms of effect of Christian religion on counseling for value re-orientation in political leadership in the country.